Cultural relevance in corporate sustainability management: a comparison between Korea and Japan - Ki-hoon Lee; David M. Herold (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2016)
Despite the increasing global popularity of corporate sustainability, a nation's culture and its effects on activities relating to corporate sustainability are little understood. From the perspective of cultural relevance, this paper investigates the similarities and differences between Korea and Japan in their practices of corporate sustainability. Using questionnaire survey data, we examine the usefulness and applicability of Hofstede's cultural values (power distance, individualism, uncertainty avoidance, masculinity and long-term orientation) to corporate sustainability management in the context of Korea and Japan. We find that Hofstede's cultural values are partially useful and applicable in explaining corporate sustainability practices. From the aspect of the integration of corporate sustainability practices, Hofstede's cultural value model was applicable, but it was not applicable in explaining cultural differences. This study is the first attempt to examine the cultural relevance of Hofstede's model in corporate sustainability management practices in a study comparing Korea and Japan. A new theoretical foundation and insights into national culture and its effect on corporate sustainability management provide a basis for further studies.
Keywords: 650; Corporate sustainability management; National culture; Cultural value; Cultural relevance; Asia